IMPROVING STUDENTS’ READING COMPREHENSION THROUGH TWO STAY – TWO STRAY LEARNING MODEL - Fitrah Alhaz Harahap (Universitas Negeri Medan, 2012)
This study deals with improving students’ reading comprehension through Two Stay – Two Stray Leaning Model. This study was conducted by using classroom action research. The subject of the research was class XI-IPA SMA GAJAH MADA Medan which consisted of 28 students. The research was conducted in two cycles and every cycle consisted of four meetings and two meetings. The instruments for collecting data were quantitative data (multiple choice test) and qualitative data (diary notes, observation sheet, questionnaire sheet, and interview). In second competence test 14 % (four students) got 70 points. It means there was an improvement for 14 %. In next competence test 86 % (24 students) got 70 points. The improvement was 72 %. It can be concluded that Two Stay – Two Stray Learning Model could improve students’ reading comprehension.